Produção de compósitos Al/AlCuFe via Spark Plasma Sintering (SPS) - Evangelista, Katherine de Souza (2021)
Quasicrystals are materials with a unique combination of mechanical and tribological properties, they have high hardness and low friction coefficient, for example. There are several applications investigated for these materials, one of them being as reinforcement in aluminum matrix composites. Aluminum and its alloys have been widely used in industry, including for applications in the aerospace industry. Therefore, the study of this composite and the development of methods of producing it is quite relevant. This project aimed to develop aluminum composites reinforced with quasicrystalline powders in order to combine the distinct characteristics of these two materials. For the present work, quasicrystalline alloys AlCuFe were produced by melting in an induction furnace. The mixture of Al+AlCuFe powders in different volumetric proportions of quasicrystal were obtained by in high-energy ball milling. Aluminum matrix composites reinforced with quasicrystalline alloys were produced using SPS (Spark Plasma Sintering) technique. The composites were characterized using XRD and SEM techinques. Microhardness and compression tests were also performed. The characterization showed the preservation of the quasicristalline phase after sintering, as well the presence of the λ crystalline phase of the AlCuFe system. Results also showed that yield strength increased with proportion of reinforcement, reaching 127.9Mpa for the sample containing 20% of reinforcement, a considerable increase, when compared to the sample without reinforcement, only 55,2Mpa. This same behavior was observed for micro hardness, which had an increase of up to 56% for the sample containing 20% of reinforcement when compared to pure aluminum. Among the composites produced in this work, the one that best combined the aluminium ductility with the quasicrystal hardness was Al+20%AlCuFe, producing a material with great density/resistance ratio. Keywords – quasicrystals, SPS, AlCuFe, composites, aluminum.